(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to know (the effect of the strategic education model on the achievement of female students with learning difficulties in mathematics and their achievement motivation) by verifying the following hypotheses:1- There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group who studied according to the strategic education model and the average scores of the students of the control group who studied according to the usual method of achievement.2- There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group who studied according to the strategic education model and the average scores of the students of the control group who studied according to the traditional method on the achievement motivation scale.